2024
DOI: 10.3390/toxics12010043
|View full text |Cite
|
Sign up to set email alerts
|

Binding Affinity and Mechanism of Six PFAS with Human Serum Albumin: Insights from Multi-Spectroscopy, DFT and Molecular Dynamics Approaches

Mingguo Peng,
Yang Xu,
Yao Wu
et al.

Abstract: Per- and Polyfluoroalkyl Substances (PFAS) bioaccumulate in the human body, presenting potential health risks and cellular toxicity. Their transport mechanisms and interactions with tissues and the circulatory system require further investigation. This study investigates the interaction mechanisms of six PFAS with Human Serum Albumin (HSA) using multi-spectroscopy, DFT and a molecular dynamics approach. Multi-spectral analysis shows that perfluorononanoic acid (PFNA) has the best binding capabilities with HSA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…To understand the binding mechanism between PFAS and transport proteins, various experimental techniques and computational studies have been used to calculate the binding constants of different PFAS [125][126][127]. Molecular docking studies have revealed the involvement of hydrophobic and hydrogen-bonding interactions of PFAS with proteins.…”
Section: Endocrine Disruptors and Kidney Disordersmentioning
confidence: 99%
“…To understand the binding mechanism between PFAS and transport proteins, various experimental techniques and computational studies have been used to calculate the binding constants of different PFAS [125][126][127]. Molecular docking studies have revealed the involvement of hydrophobic and hydrogen-bonding interactions of PFAS with proteins.…”
Section: Endocrine Disruptors and Kidney Disordersmentioning
confidence: 99%